Revitalization of Tourism in Palu Bay After the 2018 Disaster: The Role of Local Wisdom-Based Collaboration - Idham Idham; Dzulkifli Bin Mukhtar (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
Six years after the 2018 earthquake and tsunami, the tourism sector in the Palu Bay area has yet to fully recover, largely due to the absence of disaster risk–based planning. Collaboration among diverse societal elements has become essential to ensuring the sustainability of the tourism industry in this post-disaster region. The concept of collaborative governance emphasizes voluntary cooperation, horizontal cross-sectoral relationships, and the active engagement of multiple public actors in tangible social initiatives. This study adopts an interpretive qualitative approach, aiming to deeply understand social phenomena without manipulation, with data gathered through in-depth interviews, participatory and non-participatory observation, and document analysis. The analysis follows a thematic approach to identify patterns emerging from stakeholders’ perspectives. The research explores the lived experiences of communities in developing the Palu Bay tourism industry before and after the disaster, while identifying collaborative strategies to restore the sector. Findings indicate that post-disaster tourism recovery requires synergy among all societal layers—particularly religious communities—by embedding local wisdom values as the foundation for developing religious tourism. This local wisdom serves not only as a cultural asset but also as a continuous reminder that Palu City lies within the disaster-prone Pacific Ring of Fire.